Time to calcitonin normalization after surgery for node-negative and node-positive medullary thyroid cancer. Issue 4 (6th February 2019) - Machens, A; Lorenz, K; Dralle, H
Abstract: Background: It remains unclear when postoperative serum calcitonin levels should be measured in patients with medullary thyroid cancer (MTC) and, specifically, whether this decision should be based on the preoperative calcitonin level or nodal status. Methods: A cohort of patients with previously untreated MTC was studied. Kaplan–Meier analyses, stratified by preoperative calcitonin level, nodal status and number of nodal metastases, were performed to determine time to calcitonin normalization after initial surgery, with statistical analysis by means of the log rank test. Results: Some 213 patients with node-negative and 182 with node-positive MTC were included in the study. Postoperative calcitonin levels normalized in a mean of 3·5 versus 3·7 days respectively among patients with preoperative calcitonin levels of 10–100 pg/ml ( P = 0·815); 4·8 versus 5·3 days in those with preoperative calcitonin levels of 100·1–500 pg/ml ( P = 0·026); 5·3 versus 9·9 days in patients with preoperative calcitonin levels of 500·1–1000 pg/ml ( P = 0·004); and 6·6 versus 57·7 days among those with preoperative calcitonin levels exceeding 1000 pg/ml ( P < 0·001). Calcitonin levels normalized in a mean of 4·7 days when nodal metastasis was not present, 5·2 days in those with one to five nodal metastases, 7·0 days in patients with six to ten nodal metastases, and 57·1 days among patients with more than ten nodal metastases. Postoperative calcitonin normalization curves paralleled each other in patients with node-negative MTC, but diverged in those with node-positive disease and with more nodal metastases. Conclusion: Calcitonin levels typically normalize within 1 week; and within a fortnight in those with node-positive MTC and preoperative calcitonin levels of 500·1–1000 pg/ml. With node-positive MTC and preoperative calcitonin levels exceeding 1000 pg/ml, and with more than ten nodal metastases, calcitonin normalization takes longer. Abstract : Sensitive as prognostic tool